Tensile stress effect on epitaxial BiFeO3 thin film grown on KTaO3 - In-Tae Bae (Nature Portfolio, 2018)
Abstract Comprehensive crystal structural study is performed for BiFeO3 (BFO) film grown on KTaO3 (KTO) substrate using transmission electron microscopy (TEM) and x-ray diffraction (XRD). Nano-beam electron diffraction (NBED) combined with structure factor calculation and high resolution TEM images clearly reveal that the crystal structure within BFO thin film is rhombohedral BFO, i.e., bulk BFO phase. Epitaxial relationship found by NBED indicates the BFO film grows in a manner that minimizes lattice mismatch with KTO. It further suggests BFO film is under slight biaxial tensile stress (~0.35%) along in-plane direction. XRD reveals BFO lattice is under compressive stress (~1.6%), along out-of-plane direction as a result of the biaxial tensile strain applied along in-plane direction. This leads to Poisson’s ratio of ~0.68. In addition, we demonstrate (1) why hexagonal notation rather than pseudocubic one is required for accurate BFO phase evaluation and (2) a new XRD method that shows how rhombohedral BFO can readily be identified among other phases by measuring a rhombohedral specific Bragg’s reflection.